Analysis Of Financial Performance In The (KPN) Civil Sevant Cooperative In Pasar Pino Village,South Bengkulu - Nursia Regita; Ida Anggriani; kamelia Astuty (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
The aim of this research is to determine the financial performance of the civil servant cooperative (KPN) in Pasar Pino village. This research on the Civil Servant Cooperative (KPN) in Pasar Pino village used a quantitative descriptive method, which was carried out to analyze financial performance after comparing the financial reports of the 2020-2021 Civil Servant Cooperative (KPN) and using quantitative analysis techniques to manage financial data using analysis. financial ratios. The results of research on the civil servant cooperative (KPN) in Pasar Pino village, the financial reports presented were not good because they were still far below the established standards for assessing liquidity, solvency and profitability ratios. The civil servant cooperative (KPN) in Pasar Pino village does not prepare cash flow financial reports using methods, liquidity ratios, solvency and profitability so it does not know the criteria according to the 2004 Republic of Indonesia Ministry of Cooperatives, UKM, criteria for its financial reports. Therefore, researchers have analyzed the financial reports of the Civil Servant Cooperative (KPN) in Pasar Pino village in accordance with the standards for assessing liquidity, solvency and profitability ratios.